PENGGUNAAN MEDIA KARTU GAMBAR UNTUK MENINGKATKAN HASIL BELAJAR EKONOMI DI SMP - Pratita, Dewi (Parameter, 2014)
Abstract: This study aims to determine the influence of the media card to the students' pictures on subjects of Integrated Social Sciences (Economics). Methods of research using experimental research approach. The population in this study consists of 8 classes with the number of students as many as 304 students. Samples taken as many as 80 people by using a cluster sampling. Methods of data collection by using the tests and observations with a test data analysis techniques to find the average student test results and observation data analysis techniques using the t-test to test the hypothesis. The test results indicate a mean difference between experimental class with a grade of 8.35% of control. This means there is a picture card media influence the implementation of the increase in student learning outcomes. The results of analysis of observational data shows an increase of activity in learning. Abstrak: Penelitian ini bertujuan untuk mengetahui pengaruh media kartu gambar terhadap hasil belajar siswa pada mata pelajaran Ilmu Pengetahuan Sosial Terpadu (Ekonomi). Metode penelitian dengan menggunakan pendekatan penelitian eksperimen. Populasi dalam penelitian ini terdiri dari 8 kelas dengan jumlah siswa sebanyak 304 orang siswa. Sampel yang diambil sebanyak 80 orang dengan menggunakan cluster sampling. Metode pengumpulan data dengan menggunakan tes dan observasi dengan teknik analisis data tes berupa mencari rata-rata hasil tes belajar siswa dan teknik analisis data observasi mengunakan uji-t untuk menguji hipotesis. Hasil uji menunjukkan adanya perbedaan mean antara kelas eksperimen dengan kelas kontrol sebesar 8,35%. Hal ini berarti ada pengaruh penerapan media kartu gambar terhadap peningkatan hasil belajar siswa. Hasil analisis data observasi menunjukkan adanya peningkatan keaktifan siswa dalam belajar.